Global banking network and regional financial contagion. - Cyn-Young,Park (Economics Working Papers., 2018)
This paper investigates and tests the role of regional exposures in financial contagion from advanced to emerging market economies through the global banking network using data on cross border bilateral bank claims and liability positions. Results indicate that direct exposures of a countrys own and the overall regions banking sectors to crisis affected countries are systematically related to bank capital outflows during the global financial crisis. A further analysis suggests more favorable behavior of the same region lender toward emerging economies during crisis.